2020
DOI: 10.1038/s41558-020-00920-8
|View full text |Cite
|
Sign up to set email alerts
|

Fuel availability not fire weather controls boreal wildfire severity and carbon emissions

Abstract: Carbon (C) emissions from wildfires are a key terrestrial-atmosphere interaction that influences global atmospheric composition and climate. Positive feedbacks between climate warming and boreal wildfires are predicted based on top-down controls of fire weather and climate, but C emissions from boreal fires may also depend on bottom-up controls of fuel availability related to edaphic controls and overstory tree composition. Here we synthesized data from 417 field sites spanning six ecoregions in the northweste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 39 publications
7
113
1
2
Order By: Relevance
“…While other studies predict fuel and climate to be the drivers in Equatorial Asia 33 , we found that precipitation alone explained the variability in fires in this region. In Boreal areas, we find an important effect of fuel load, which is not predicted by previous models, but consistent with observations 59 . In Southeast Asia, Abatzoglou et al 33 find aridity alone as a driver, whereas we find climate, fuel, as well as population density to be important drivers.…”
Section: Discussionsupporting
confidence: 88%
“…While other studies predict fuel and climate to be the drivers in Equatorial Asia 33 , we found that precipitation alone explained the variability in fires in this region. In Boreal areas, we find an important effect of fuel load, which is not predicted by previous models, but consistent with observations 59 . In Southeast Asia, Abatzoglou et al 33 find aridity alone as a driver, whereas we find climate, fuel, as well as population density to be important drivers.…”
Section: Discussionsupporting
confidence: 88%
“…Alternately, the loss of accumulated peat due to wildfire may be affected by interacting processes related to peat depth, peat properties, and WT draw down. Organic soil depth has been linked to burn severity (e.g., depth of burn or carbon loss) for shallow organic soils (Shetler et al, 2008; Walker et al, 2020). Moreover, higher average depth of burn has been observed at peatland margins (Hokanson et al, 2016), where small, perched peatlands tend to have deeper WT at their edges (Hokanson et al, 2020) and the WT is more likely to drop below the peat profile.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the strongest driver of per area emissions of C in boreal wildfires appears to be total fuel (i.e. potentially combustible organic material) which is strongly controlled by long term forest moisture (Walker et al, 2018(Walker et al, , 2020. However, in order for this fuel to be available to ignite and propagate fire it must be sufficiently dried and spatially arranged to be susceptible to high heat and oxygen exposure during active fire.…”
Section: Introductionmentioning
confidence: 99%
“…This field sampling has been regionally limited and biased towards a few high intensity burn complexes in North America which may in turn bias global emission estimates (van Leeuwen et al, 2014). For example, the Eurasian boreal region is dominated by relatively fire resistant vegetation that promotes lower intensity fire (Rogers et al, 2015;de Groot et al, 2013a) and C loss (0.88 kgC/m 2 ) (Ivanova et al, 2011) than that in typical (Walker et al, 2020) North American wildfire (3.3 kgC/m 2 ) (Boby et al, 2010). Though Eurasia contains over 70% of the boreal global land area (de Groot et al, 2013a), and about 50% (20 Mha/yr) of its yearly burnt area (Rogers et al, 2015), wildfire emissions from this region are severely under sampled in the field (van Leeuwen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation